19‐VNTR loci used in genotyping Chinese clinical Mycobacterium tuberculosis complex strains and in association with spoligotyping. (15th January 2013) - Jiang, Yi; Liu, Hai‐can; Zheng, Huajun; Dou, Xiangfeng; Tang, Biao; Zhao, Xiu‐qin; Zhu, Yongqiang; Lu, Bing; Wang, Shengyue; Dong, Hai‐yan; Zhang, Yuan‐yuan; Zhao, Guoping; et al.
<x xml:space="preserve">Abstract</x> Recently, tandem repeat typing has emerged as a rapid and easy method for the molecular epidemiology of the Mycobacterium tuberculosis (M. tuberculosis) complex. In this study, a collection of 19 VNTRs incorporating 15 previously described loci and 4 newly evaluated markers were used to genotype 206 Chinese M. tuberculosis isolates and 9 BCG strains. The discriminatory power was evaluated and compared with that obtained by Spoligotyping. It turned out that 15‐locus VNTR could be very useful in M. tuberculosis complex strains genotyping in China. The 4 newly evaluated loci were proved informative and could be useful for future epidemiology studies, especially in Beijing family strains. In addition, a unique pattern of the latter 4 loci were found in Chinese BCG strains.